2015
DOI: 10.1016/j.marenvres.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on Mediterranean sea urchin embryonal development is species specific and depends on moment of first exposure

Abstract: With the ever growing use of nanoparticles in a broad range of industrial and consumer applications there is increasing likelihood that such nanoparticles will enter the aquatic environment and be transported through freshwater systems, eventually reaching estuarine or marine waters. Due to silver's known antimicrobial properties and widespread use of silver nanoparticles (AgNP), their environmental fate and impact is therefore of particular concern.In this context we have investigated the species-specific eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…In Strongylocentrotus droebachiensis, Ag + , AgNPs and f-SWCNTs, separately and in mixtures, induced different developmental defects in exposed embryos (Magesky and Pelletier, 2015). Burić et al (2015) showed that the effects of AgNPs on embryonal development in (1-10 μg/L) .Moreover, the greatest impact on development was noted for those embryos first exposed to NPs at 6 and 24 h post fertilization, this underlying how the timing of exposure to NPs may represent an important factor in the development of abnormalities.…”
Section: Effects On Developmentmentioning
confidence: 99%
“…In Strongylocentrotus droebachiensis, Ag + , AgNPs and f-SWCNTs, separately and in mixtures, induced different developmental defects in exposed embryos (Magesky and Pelletier, 2015). Burić et al (2015) showed that the effects of AgNPs on embryonal development in (1-10 μg/L) .Moreover, the greatest impact on development was noted for those embryos first exposed to NPs at 6 and 24 h post fertilization, this underlying how the timing of exposure to NPs may represent an important factor in the development of abnormalities.…”
Section: Effects On Developmentmentioning
confidence: 99%
“…Pioneering eco-toxicological and immuno-toxicological experimental studies were carried out with free-living P. lividus by Matranga et al (2006); Pinsino et al (2008), , and Migliaccio et al (2019). Nevertheless, most of the research on the ecotoxicity of ENMs on sea urchins thus far has been focused on the embryonic development and carried out according to classical toxicological criteria: dose-and time-dependent responses, analysis of the effects on development and analysis of the tissues accumulating nano/micromaterial such as metaloxide, metal, carbon-based particles (Fairbairn et al, 2011;Buric et al, 2015;Mesaric et al, 2015;Alijagic and Pinsino, 2017). However, precise and predictive linkages between laboratory and natural exposures (unrealistic and realistic) have not yet been established, and future work on sunscreen residues should tackle these points, considering for example direct and indirect release into the sea and the possible transformations underwent before internalisation by living organisms.…”
Section: Biological Effects On Marine Organismsmentioning
confidence: 99%
“…It is also important to experiment wider ranges of concentrations of nanoparticles and to test the feasibility in the application of nanoparticles in large aquaculture systems, perhaps adding the nanoparticles as food additives. An adverse effect of AgNP on coastal biota has been recently shown (Burić et al, 2015;Degger et al, 2015;Gambardella et al, 2015;Rocha et al, 2015), but fortunately Juárez- Moreno et al (2017) had demonstrated that AgNPs at therapeutic doses are not toxic, and does not affect the metabolic rate or total hemocytes count in juvenile Litopenaeus vannamei. However, given the high variety of metals and metalloids used as nanoparticles, it is important to study the impact of their use on aquaculture species, human health, and the coastal environment, to implement future strategies to develop a sustainable and responsible aquaculture.…”
Section: Discussionmentioning
confidence: 99%